New Teacher Perceptions of Inclusive Practices: An Examination of Contemporary Teacher Education Programs - Soleas, Eleftherios Kyprianos (Alberta Journal of Educational Research, 2016)
This article details a sequential explanatory mixed-method study into the perceptions of 44 new teachers regarding inclusive practices from their teacher education program, as well as their relative intent to utilize them in their practice. The purpose of this study was to determine the self-perceived capacity of the next generation of teachers leaving a Canadian teacher education program from a mid-sized university in Southern Ontario. As new teachers are the product of contemporary teacher education programs, their lingering needs and perceptions are potential avenues for intervention in continuing the refinement of teacher education. First, a complete audit of relevant teacher education was performed, followed by participants completing a mixed-methods survey. Then, these survey findings informed critical-case interviews. Analyses yielded two groups of themes: confidence from teacher education, and the lingering needs of new teachers. These data suggest that teacher education programs are not entirely effective at producing new teachers who are confident in their abilities to be inclusive practitioners in the classroom. Further, the perceptions of new teachers illustrate avenues for intervention in making teacher education programs more effective. Cet article présente en détail une étude exploratoire à méthodologie mixte portant sur les perceptions de 44 nouveaux enseignants quant aux pratiques inclusives de leur programme de formation et leurs intentions de les intégrer à leur pratique. L’objectif de cette étude était de déterminer l’auto-évaluation qu’établit la prochaine génération d’enseignants de leur capacité au terme de leur programme de formation dans une université de taille moyenne dans le Sud de l’Ontario. Les nouveaux enseignants étant le produit des programmes de formation contemporains, leurs perceptions et leurs besoins persistants représentent des pistes d’intervention possibles pour l’amélioration continue de la formation des enseignants. Une vérification complète des programmes de formation en question a d’abord été effectuée. Les participants ont ensuite complété un sondage à méthodologie mixte. Par la suite, les résultats du sondage ont servi dans les entrevues portant sur les cas importants. Les analyses ont fait ressortir deux grands thèmes : la confiance des enseignants relative à leur programme de formation et les besoins persistants des nouveaux enseignants. Ces données laissent supposer que les programmes étudiés ne sont pas entièrement efficaces dans la formation d’enseignants quant à leur confiance d’intégrer des pratiques inclusives dans leurs salles de classe. Les perceptions des nouveaux enseignants offrent des pistes d’intervention visant l’amélioration des programmes de formation.